Pathways to Better Health? Assessing the Impact of Ethiopian Community-Based Health Insurance on Children Health Outcomes - Zecharias Anteneh; Martina Celidoni; Lorenzo Rocco (Global Labor Organization (GLO), 2023)
Publicly financed Community Based-Health Insurance (CBHI) schemes are typically implemented in developing countries to foster healthcare utilization and improve health outcomes among low-income households. Using the Demographic and Health Survey from 2005 to 2016, we estimate the effects of the Ethiopian CBHI on children's health. Difference-in-differences estimates show that CBHI reduced mortality and the probability of being underweight among children under five. We also find that CBHI significantly reduces wasting, a measure of short-term nutritional deficiency or health conditions, but not stunting, known to be an indicator of long-term chronic malnutrition. Potential mechanisms underlying our results are improved maternal health, access to health care, nutrition and a reduced risk of poverty.
Keywords: G52; I13; J13; 330; community-based health insurance; children health; infant feeding; Difference in Differences approach